Effect Of Repeated Near Field Earthquake To The High-Rise Rc Building - Ade Faisal, Ph.D (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
Nowadays, most of the analyst and designer consider ‘rare’ single earthquake in seismic analysis and design. The repeated earthquakes are ignored even though the actual earthquake event occurs repetitively and the effect of the repeated earthquake is qualitatively acknowledged. Repeated earthquake is the repetition of medium-strong earthquakes at short time interval. The repeated earthquake was reported in many part of the world. This study investigates the effect of this event on the response of the reinforced concrete (RC) buildings. For that purpose, this study uses five generic RC models with different behaviour factor, q (i.e. 1, 1.5, 2, 4 and 6) in which the model with q = 1 is the strongest building and the strength of the building decreases with the increase of the q value. Furthermore, all models are 18-storey to represent high rise buildings in three dimensional in order to consider the effect of earthquake in orthogonal direction. There are 40 repeated near field ground motions which were combined randomly from 20 single near field ground motions employed in this study and 20 residual ground motion records. These repeated earthquakes are divided into two case, i.e. case 2 and case , in which case 2 has two consecutive earthquake(i.e. main shock and aftershock) and case 3 has three consecutive earthquakes (i.e. foreshock, main shock and aftershock). The duration between two consecutive earthquakes is 100s which is enough for the model to cease the motion.  The near field earthquake contains special characteristic which is known as pulse effect that far field earthquake do not has, therefore, this study investigates also the effect of pulse period on the response of the RC buildings. The displacement ductility and storey ductility demand were considered to assess the response of the RC models and they are computed by using  nonlinear time history analysis. It was found that repeated near field earthquake give significant effect to the respond of high-rise RC buildings compared to single near field earthquake.